21‐3: 3D Interactive System Based on Vision Computing of Direct‐flective Cameras. Issue 1 (May 2016) - Li, Xuan; Chen, Chun-Ho; Hsu, Yi-Chun; Huang, Yi-Pai
Abstract : A bare finger 3D air‐touch interactive technology for portable devices is developed. Using directive‐flective optical design on camera modules, the interactive range is workable from 1.5 cm to 50 cm above the entire surface of the display. Moreover, the motion vision computing, different from skin color detection, is presented to determine the position of fingertips. The position mean errors are of less than 1 cm. This accuracy realizes a camera‐based interactive system allowing for near‐distance 3D air‐touch functionality. Therefore, floating 3D images can be touched and interacted with, potentially creating more application and intuitive human machine interface.